KEJADIAN STRESS KERJA PADA PERAWAT RAWAT INAP. APAKAH BEBAN KERJA MEMILIKI PENGARUH? - Dwijayanto, I Made Rio; Azuma, Anindita Paramastuti; Putra, Ryryn Suryaman Prana; Abdullah, Asmiwarti (Ensiklopedia of Journal, 2025)
The stress experienced by nurses in carrying out their duties has a significant effect on the quality of nursing care provided to patients. Stress in nurses can be caused by heavy workloads. The purpose of this study was to determine the relationship between workload and the incidence of work stress in inpatient nurses. A cross-sectional study design was used in this study. The study was conducted in a hospital in South Sumatra Province. The research was conducted in September 2024. The research population consisted of all nurses at the hospital. The sample size was 48 people. The sampling technique used total sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between workload and work stress (p value: 0.042). It is recommended that the hospital and nurses improve work stress management through counseling services, training, and psychoeducation on stress management. Keywords: Workload, Nurses, Work Stress